On Maintaining National Identity and Cultural Heritage in European Integrations: Basic Misconceptions and Important Possibilities - Miloš Milenković (University of Belgrade, 2016)
Keeping in mind the present transcendence of the national/democratic dichotomy and the recent turn from governmental to cultural elites in the policies of the EU and the European Council directed at the Republic of Serbia, the paper recommends a new field of application of ethnology and anthropology, based on previous analyses and modifications of identity policies of the EU. The foundation of the baseless idea of Europe as a framework in which national identities and cultural heritage are weakened and even disappear will be considered, and the fact that the EU is the largest global consumer of identity will be pointed out, along with the possibilities this brings to the domain of maintaining the national identity and cultural heritage of the citizens of Serbia. Ethnologists and anthropologists can participate in this process not only professionally, as researchers, or privately as political actors, but also in the domain of the application of science, helping culturally legitimate elites recognize that the protection of national identities and cultural heritage within the confines of an international budget is a lucrative, sustainable and efficient way to maintain interpretative sovereignty, especially in times of crisis for national budgets. Seeing as trained ethnologists and anthropologists are professionally trained for consulting in the domain of identity issues, they are in the unique position to point both sides in the process of European integrations toward the huge potential within further redirecting of incentives toward culturally legitimate elites.